Bagaimana Mahasiswa NU Memahami Islam Moderat? - Benny Afwadzi; Miski Miski; Mila Aulia; Roudlotul Jannah (Lembaga Penelitian, Publikasi dan Pengabdian kepada Masyarakat (LP3M), STIT Islamiyah Karya Pembangunan Paron, Ngawi, Jawa Timur, 2023)
Abstract: This research is motivated by many scholars who challenge NU, which is considered a moderate Islamic organization, and the meanings of the word moderate vary. On the other hand, moderate Islam is a solution to many students' radical thoughts and terror. By taking Unisma as the research object, this article focuses on two topics: NU students' interpretation of moderate Islam and the factors that influence this interpretation. This article is qualitative research using in-depth interviews with 12 students with various study program characteristics. The findings obtained from this study are, first, NU students interpret moderate Islam with three models: teachings, nation and state, and relations with modernity. These three understandings are separate from NU's moderate principles. Most NU students accept moderate Islamic terminology, but a small number of them reject it. Second, the moderatism of NU students is influenced by many factors, including family background, education, social media, environment, and association. Furthermore, this study accepts that moderatism in NU is not on the same line but also rejects research suggesting that NU students tend to be radical and intolerant. And association. Furthermore, this study accepts that moderatism in NU is not on the same line but also rejects research suggesting that NU students tend to be radical and intolerant. And association. Furthermore, this study accepts that moderatism in NU is not on the same line but also rejects research suggesting that NU students tend to be radical and intolerant. Keywords: Doctrine, Moderate Islam, Modernity, Nation and State, NU students. Abstrak: Penelitian ini dilatarbelakangi oleh banyak sarjana yang memberikan tantangan pada NU yang dianggap sebagai organisasi Islam moderat dan pemaknaan terhadap kata moderat yang bervariasi. Di sisi lain, Islam moderat merupakan solusi atas pemikiran radikal dan teror yang banyak dimiliki oleh mahasiswa. Dengan mengambil Unisma sebagai objek penelitian, artikel ini fokus pada dua topik, yakni interpretasi mahasiswa NU terhadap Islam moderat dan faktor-faktor yang mempengaruhi interpretasi tersebut. Artikel ini adalah penelitian kualitatif dengan metode wawancara mendalam kepada 12 mahasiswa dengan karakter program studi yang bervariasi. Temuan yang didapatkan dari penelitian ini adalah, pertama, mahasiswa NU menginterpretasikan Islam moderat dengan tiga model: ajaran, berbangsa dan bernegara, dan relasi dengan modernitas. Ketiga pemahaman tersebut tidak bertentangan dengan prinsip-prinsip moderat NU. Sebagian besar mahasiswa NU menerima terminologi Islam moderat, namun sebagian kecil dari mereka menolaknya. Kedua, moderatisme mahasiswa NU dipengaruhi oleh banyak faktor, diantaranya adalah latar belakang keluarga, pendidikan, media sosial, lingkungan, dan pergaulan. Lebih jauh, penelitian ini menerima anggapan bahwa moderatisme di NU tidak berada pada satu garis yang sama, tetapi juga menolak penelitian menyebut bahwa mahasiswa NU cenderung radikal dan intoleran. Kata Kunci: Ajaran, Bangsa dan Negara, Islam Moderat, Mahasiswa NU, Modernitas.